2015
DOI: 10.1039/c5nj00094g
|View full text |Cite
|
Sign up to set email alerts
|

4-Aminoquinoline-pyrimidine-aminoalkanols: synthesis, in vitro antimalarial activity, docking studies and ADME predictions

Abstract: Twenty-four new 4-aminoquinoline-pyrimidine hybrids containing a terminal aliphatic amino-alcohol chain were synthesized and assessed for their antimalarial activity against chloroquine-sensitive (D6) and chloroquine-resistant (W2) strains of Plasmodium falciparum. All of the compounds displayed potent antiplasmodial activities (IC 50 values in the range of 0.05-10.47 mM) with no appreciable cytotoxicity towards mammalian cells, up to the highest tested concentration of 12 mM. Molecular docking studies of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Molecular docking was performed by using default settings of Maestro v‐11.4. Selected proteins 1J3K , 3QG2 , and 3QGT were auto‐downloaded via software under the specific organism P. falciparum . The expression system of E. coli was performed under systematic steps, as follows: default setting and flexible space of ligands were validated by comparison of biological activity, and GlideScore, docking parameter, and best docked ligands were fit into the cavities with lower energy score.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking was performed by using default settings of Maestro v‐11.4. Selected proteins 1J3K , 3QG2 , and 3QGT were auto‐downloaded via software under the specific organism P. falciparum . The expression system of E. coli was performed under systematic steps, as follows: default setting and flexible space of ligands were validated by comparison of biological activity, and GlideScore, docking parameter, and best docked ligands were fit into the cavities with lower energy score.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with compounds 116 (Figure ), the regio‐isomers 117 (IC 50 : 207‐883 nM) showed higher activity against CQR Dd2 strain. Replacement of chloro at pyrimidine by nitrogen‐containing heterocycles ( 118 and 199 ) could increase the activity against CQR Dd2 strain to some extent, but aminoalkanols reduced the activity . Similar SARs were also observed for quinoline‐pyrimidine hybrids 120 to 122 (IC 50 : 120‐440, 140‐240, and 5‐30 nM against CQS 3D7 strain, respectively; 500‐700, 580‐1,170, and 16‐210 nM against CQR Dd2 strain, respectively), quinoline‐pyrimidine hybrids 123 to 130 ( 123 and 124 attaching furan skeleton, IC 50 : 38‐61 and 39‐257 nM against CQS 3D7 and CQR Dd2 strains, respectively; 125 and 126 with piperonyl fragment, IC 50 : 20‐150 and 50‐990 nM against CQS 3D7 and CQR Dd2 strains, respectively; 127 and 128 with pyridine motif, IC 50 : 30‐1193 and 39‐1143 nM against CQS 3D7 and CQR Dd2 strains, respectively; 129 and 130 with thiophene motif, IC 50 : 32.8‐83.7 and 18.9‐409.1 nM against CQS 3D7 and CQR Dd2 strains, respectively) bearing an aromatic ring at the amino near to pyrimidine moiety, and quinoline‐pyrimidine hybrids 131 (IC 50 : 32‐204 and 32‐1018 nM against CQS 3D7 and CQR Dd2 strains, respectively), 132 (IC 50 : 19‐6022 and 46‐9994 nM against CQS 3D7 and CQR Dd2 strains, respectively) incorporating modified anilines at the pyrimidine end.…”
Section: Quinoline Hybridized With Novel Antimalarial Pharmacophores mentioning
confidence: 61%
“…The basic notion of covalently linking the antimalarial 4‐aminoquinoline (hemozoin formation inhibitor) and pyrimidine (plasmodial DHFR inhibitor) pharmacophores was to generate a more potent molecule which may have the ability to simultaneously act on both the parent targets. Based on our previous studies, following structure‐activity relationships were observed: (i) replacement of diamine linker by a rigid linker (piperazine) diminishes antimalarial activity; (ii) removal of 6‐methyl group in pyrimidine ring reduces antimalarial activity; (iii) substitution of the carbocyclic amine attached to pyrimidine ring by aminoalkanol‐substitutions reduces activity, but improves the resistance index (RI: ratio of antiplasmodial IC 50 values of resistance vs sensitive strain); (iv) docking studies conducted on Pf ‐DHFR revealed that H‐bonding substituents present in the aminoalkanol‐substituent of pyrimidine ring showed favourable docking interactions with active site residues . Based on the above viewpoints and in anticipation that the synthesized hybrids may have improved antiplasmodial activity against the plasmodial strains without showing any signs of development of cross‐resistance (i. e. having RI ≅ 1), the present series of compounds were synthesized (Figure ).…”
Section: Resultsmentioning
confidence: 99%